In Pursuit of Better Sheltering and Housing After Disasters: The Architectural Perspective Through Ideas Competitions - Didem Güneş Yılmaz (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
In the past, post-disaster sheltering, and rehousing involved a limited field of expertise. Architecture was deemed loosely related to the context. Today, architecture involves in post-disaster issues more than ever and does that in collaboration with other disciplines. It uses technological developments in any field related that can bring better solutions to post-disaster shelter crises. For the past few years, many architectural competitions were launched within this theme. Architectural competitions aim to find the most appropriate design for a problem through the accumulation of wide range of ideas in a short period of time that would not be possible if a case assigned to only one architect. This can be deemed as an indirect way of participatory approach in post-disaster sheltering and housing with the inputs of professionals and students. Eventually, the architectural competitions became the arena of this pursuit since architecture began to step out of the comfort zone and started to ‘design’ for people in need, for emergencies and for rebuilding for societies after long trouble times in disastrous areas. The paper reviews a range of competitions fall under the topics of post-disaster sheltering and rehousing by examination of the outstanding projects.